The selection of auditor firms by companies in the new issue market - Firth, Michael; Andrew, Andrew; Smith (School of Management Working Papers, 1991)
The paper provides some empirical evidence on the question of product differentiation in the market for audits. Using agency cost and signalling frameworks we posit that there will be a demand for varying levels of audit quality. Because audit quality is not directly observable to investors we postulate that quality will be proxied by the auditor's brand name reputation. Big Eight auditors are categorised as being high quality producers. Using data on companies newly listing on the New Zealand Stock Exchange we test the derived models of auditor choice. Auditor choice is a dummy variable (0,1) partitioned on the basis of non Big Eight and Big Eight accounting firms. The results provide support for the idea of product differentiation in the market for audits.